Haptic and Audio Interaction Design 6th International Workshop, HAID 2011, Kusatu, Japan, August 25-26, 2011. Proceedings - Cooper, Eric; Brewster, Stephen; Ogawa, Hitoshi; Kryssanov, Victor K. (Information Systems and Applications, incl. Internet/Web, and HCI ;, 2011)
This book constitutes the refereed proceedings of the 6th International Workshop on Haptic and Audio Interaction Design, HAID 2011 held in Kusatsu, Japan, in August 2011. The 13 regular papers and 1 keynote presented were carefully reviewed and selected for inclusion in the book. The papers are organized in topical sections on haptic and audio interactions, crossmodal and multimodal communication and emerging multimodal interaction technologies and systems.